LEGAL BOUNDARIES OF ACTING GOVERNORS AND DEMOCRATIC LEGITIMACY IN WEST PAPUA’S LOCAL GOVERNANCE - Isak Semuel Kejne Mansawan; Faisal Abdullah; Abdul Razak; Filep Wamafma; Elsye Yubilia Keysinaya (Institut Agama Islam Negeri Bone, 2026)
Acting Governors (Pj Governors) in Indonesia, including in West Papua, are temporary officials appointed to fill vacancies in regional head positions based on statutory provisions. Their existence is crucial to ensure the continuity of local governance. However, in practice, the role of Acting Governors often raises issues concerning political legitimacy, governance effectiveness, and the legal implications of their authority. This study analyzes the legal basis and scope of authority of the Acting Governor of West Papua, examines its implementation in regional governance practice, and formulates recommendations for improving effective, transparent, and accountable governance. This research employs empirical legal research with a juridical-normative and conceptual approach, supported by qualitative descriptive analysis through legislation review, interviews, and documentation. The findings show that the authority of Acting Governors is normatively well-regulated, yet its implementation still faces challenges such as limited technical regulations, weak institutional capacity, and local political pressures influencing decision-making processes. Therefore, strengthening regulatory frameworks, enhancing transparency and accountability, and optimizing coordination between central and regional governments are necessary. These efforts are expected to ensure more stable, effective, and balanced governance between national and regional interests, while also supporting sustainable development and improving public service quality in West Papua in particular effectively.